Three Years Data of Uterine Fibroids Patient Characteristics at West Java Top Referral Hospital - Azzahra, Mutiara; Gondodiputro, Sharon; Amarullah, Mulyanusa (Althea Medical Journal, 2017)
Background: Uterine fibroids are the most common benign tumor in female reproductive system and a major cause in declining their quality of live. Patient characteristics has high prevalence in black women, 40s, nulliparous, and early menarche. These characteristics are varied in some areas and considered in treatment decisions. The objectives of this study was to describe the uterine fibroid patient characteristics at Dr. Hasan Sadikin General Hospital, Bandung from 1 January 2013 to 31 December 2015.Methods: A descriptive study was conducted to 255 medical records of patients with uterine fibroids at Dr. Hasan Sadikin General Hosiptal, Bandung from 1 January 2013 to 31 December 2015. This study was conducted from September to November 2016. The variables were the year of treatment, age, education, occupation, married status, menarche, abortion, parity, type of uterine fibroids, and treatment. The collected data were analyzed and presented using frequency tables and percentages.Results: Most cases of uterine fibroids were discovered in 2014. The most characteristics with uterine fibroids were pre-menopausal age (41.18%), high school education (55.69%), housewife (63.14%), normal menarche (54.51%), married (92.16%), nulliparous (47.45%), no abortion (76.47%), multiple uterine fibroids (46.67%), and hysterectomy (58.04%).Conclusions: The most combination of characteristics of patients with uterine fibroids is nulliparrous women in reproductive and pre-menopausal age with normal menarche.Â